Clinical impact of a novel device delivery system in the diagnosis of bile duct lesions: A single‐center experience. Issue 7 (20th April 2022) - Matsumori, Tomoaki; Uza, Norimitsu; Shiokawa, Masahiro; Maruno, Takahisa; Nishikawa, Yoshihiro; Morita, Toshihiro; Kuwada, Takeshi; Marui, Saiko; Okada, Hirokazu; Taura, Kojiro; Kodama, Yuzo; Seno, Hiroshi
Abstract: Background and Aim: Pathological evaluation is essential for the diagnosis of biliary tract diseases. However, existing evaluation methods have various challenges in terms of operability and diagnostic performance. The present study aimed to evaluate the feasibility, utility, and safety of a novel device delivery system for bile duct biopsy. Methods: This study was conducted as a retrospective, descriptive analysis at a single center. Overall, 25 examinations in 14 consecutive patients who underwent transpapillary biopsies for biliary lesions using the novel device delivery system from July to November 2020 were reviewed. Number and time of biopsy, technical success rate, adequate tissue sampling rate, adverse events, and diagnostic performance of bile duct biopsies using the novel device were evaluated. Moreover, negative surgical margins were assessed in patients who underwent surgical resection after mapping biopsy. Results: The median number of biopsy samples was five (range: 2–13), with a median biopsy time of 11.6 min. The technical success rate was 100% (140/140), with an adequate sampling rate of 82.9% (116/140). These rates did not differ depending on the biopsy site or purpose. There were no serious adverse events related to the procedures. The diagnostic sensitivity, specificity, and accuracy of biliary stricture were 90%, 100%, and 92.3%, respectively. Negative surgical margins were confirmed in all patients undergoing surgical resection, including one patient with a surgical procedure changed based on the results of mapping biopsy. Conclusions: The novel device delivery system has potentials in diagnosing biliary tract diseases and determining appropriate treatment strategies.